PERAN GREEN TRUST DALAM MEMEDIASI GREEN PERCEIVED VALUE TERHADAP GREEN PURCHASE BEHAVIOR PADA PRODUK ORGANIK - Putra, I Putu Agus Surya Setiawan; Suryani, Alit (E-Jurnal Manajemen, 2015)
Damage to the environment make a change in lifestyle of the people who now pay more attention to the environment, and healthy living trend has motivated people to start a movement of healthy life by consuming organic products. The purpose of this study is to analyze and explain the effect of green perceived value on green purchase behavior mediated by green trust. The population in this study was people who consume organic products in the city of Denpasar. The sampling method used was purposive sampling, the number of respondents as many as 110. Analysis technique used is path analysis and the Sobel test. The results showed that green trusts was significantly positively in mediating the effects of green perceived value to the green purchase behavior on organic products in the city of Denpasar. With this study, it is expected that marketers of organic products should inform the public about the benefits of consuming organic products, and on the other side is expected to farmers of organic products should maintain product quality in order to stay good.
Keywords: Green Perceived Value, Green Trust, Green Purchase Behavior